PENGARUH STRUKTUR DAN KARAKTERISTIK DEWAN DIREKSI DANKOMITE AUDIT TERHADAP KEBIJAKAN KEPUTUSAN DIVIDEN - Arasy Padil, Muhammad Nawawy; Adawiyah, Wardatul (Jurnal Vokasi Indonesia, 2019)
This study analyzes the structure and characteristics of the board of directors and audit committee against the policy of corporate dividend decisions on the Indonesia Stock Exchange. The method used in this study is LS regression modeling and logit regression. LS regression modeling is done to see the composition of the structure and characteristics of the board and audit committee against the dividend of the company's payment ratio and company’s dividend decision on the Indonesia Stock Exchange. Logit regression modeling is performed to see the composition and characteristics of the board of commissioners and audit committee on decisions of company dividends on the Indonesia Stock Exchange. The two regressions are expected to replace each other's regression results with each other. In this study it was found that the number of directors, the composition of female directors, and the number of independent directors had significant influence on companies to pay dividends and influence the rate of payment of dividend payment ratios.